Short and Long-Term Effects of Growth Hormone in Children and Adolescents With GH Deficiency - Ranke, Michael B. (Frontiers in Endocrinology, 2021)
The syndrome of impaired GH secretion (GH deficiency) in childhood and adolescence had been identified at the end of the 19th century. Its non-acquired variant (naGHD) is, at childhood onset, a rare syndrome of multiple etiologies, predominantly characterized by severe and permanent growth failure culminating in short stature. It is still difficult to diagnose GHD and, in particular, to ascertain impaired GH secretion in comparison to levels in normally-growing children. The debate on what constitutes an optimal diagnostic process continues. Treatment of the GH deficit via replacement with cadaveric pituitary human GH (pit-hGH) had first been demonstrated in 1958, and opened an era of therapeutic possibilities, albeit for a limited number of patients. In 1985, the era of recombinant hGH (r-hGH) began: unlimited supply meant that substantial long-term experience could be gained, with greater focus on efficacy, safety and costs. However, even today, the results of current treatment regimes indicate that there is still a substantial fraction of children who do not achieve adult height within the normal range. Renewed evaluation of height outcomes in childhood-onset naGHD is required for a better understanding of the underlying causes, whereby the role of various factors - diagnostics, treatment modalities, mode of treatment evaluation - during the important phases of child growth - infancy, childhood and puberty - are further explored.